MATH SOLVE

2 months ago

Q:
# (polynomials) multiply. (x^2-5x)(2x^2+x-3)A. 2x^4 - 9x^3 - 9x^2 - 15xB. 2x^4 + 9x^3 - 8x^2 + 15xC. 4x^4 + 9x^3 - 8x^2 + 15xD. 2x^4 - 9x^3 - 8x^2 + 15x

Accepted Solution

A:

Answer:2x^4 - 9x^3 -8x^2 + 15xStep-by-step explanation:(x^2-5x)(2x^2+x-3) distribute first2x^4x^2 + x = x^35 * 2x^2 x= 10x^35x^1+1 = 5x^25 * 3x = 15x Put them all together2x^4 + x^3 - 3x^2 - 10x^3 - 5x^2 + 15x Like terms2x^4 + x^3 -10x^3 - 3x^2- 5x^2 + 15x Add similar terms= 2x^4 + x^3 - 10x^3 - 8x^2 + 15x more adding terms2x^4 - 9x^3 -8x^2 + 15xHope my answer has helped you, if not i'm sorry.